Neisseria gonorrhoeae antimicrobial susceptibility testing: application of traditional agar dilution to a high-throughput 96-well microtiter assay - Joyce E. Kuipers; Laura Seidel; Nicole E. Garnier; Cezar M. Khursigara (Microbiology Spectrum, 2025)
ABSTRACT The global rise in Neisseria gonorrhoeae infections and increasing antimicrobial resistance underscores the urgent need for accessible and efficient antimicrobial susceptibility testing methods. While accurate, the gold standard agar dilution method is labor-intensive and resource-demanding, limiting its practicality for research. To address this, we developed and validated a high-throughput 96-well microtiter assay as a viable alternative for measuring minimum inhibitory concentrations (MIC). In addition, we assessed the use of the simple-defined Kellogg’s supplement compared to the CLSI-recommended complex-defined growth supplement. Using 17 standard laboratory strains with different resistance profiles, we evaluated the assay against azithromycin, ceftriaxone, ciprofloxacin, and gentamicin. Both 96-well microtiter assays demonstrated no major errors for any antimicrobial, with some minor errors with azithromycin and consistent minor errors with gentamicin. Essential agreement (EA) and categorical agreement (CA) ranged from 33% to 100%, with gentamicin contributing the most variability across methods. This study establishes the 96-well microtiter assay with Kellogg’s supplement as a reliable and scalable tool for N. gonorrhoeae antimicrobial susceptibility testing, reducing the time and resources required for resistance profiling.IMPORTANCEThe rapid emergence of antimicrobial resistance in Neisseria gonorrhoeae presents a critical challenge for global public health. Accurate and accessible methods for assessing antimicrobial susceptibility are essential for monitoring resistance trends and guiding effective treatment strategies. However, traditional methods, such as agar dilution, are labor-intensive and resource-intensive, limiting their widespread application in research. Our study introduces a 96-well microtiter assay that simplifies and scales up susceptibility testing while maintaining the accuracy of the gold standard. By validating the use of the simpler alternative, Kellogg’s supplement, we further lower the barriers to adoption in research settings. This innovation supports timely and efficient antimicrobial resistance surveillance and enhances the capacity for high-throughput testing of novel therapeutic compounds. By increasing the feasibility of susceptibility testing, this method can potentially improve response strategies against drug-resistant gonorrhea and other fastidious pathogens.